A System For Monitoring Indoor Air Quality Based On The Internet Of Things - Aji Nurrohman; Berliyanto Berliyanto; Sigit Wibisono; Surya Darma; Wibisono Wibisono; Leni Devera Asrar; Triyono Budi Santoso (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2024)
In this era of rapidly evolving information technology, the need to monitor and manage indoor air quality is becoming increasingly important. Poor air quality can have a negative impact on human health and productivity. Therefore, this research aims to design and implement an Internet of Things (IoT)-based Indoor Air Quality Monitoring System. The proposed system uses sensors connected to the IoT network to measure air quality parameters, such as temperature, humidity, particle content, and certain gases. The data collected by these sensors will be sent in real-time to a server via an internet connection. The server will process the data and present it in a form that can be accessed through a web interface. The implementation of IoT allows for more efficient and accurate monitoring, and provides easy access to data remotely. Users can monitor indoor air quality through their mobile devices or personal computers. The use of IoT technology in this monitoring system is expected to increase responsibility and awareness of indoor air quality. The results of this research are expected to contribute to the development of innovative solutions to improve the health and comfort of indoor environments. The conclusion of this research includes evaluation of system performance, analysis of the data generated, as well as potential development and improvement for further research.